Green synthesis of geopolymeric materials using Musina Copper Mine Tailings: a case of beneficial management of mine tailings - Matidza, Murendeni (My University, 2019)
Mine tailings (MT) have been a global problem due to the environmental impacts the waste generates such as air, soil and water pollution. The detrimental impacts include a global problem such as acid mine drainage (AMD) which has been difficult to cleanup. Several studies have been conducted to find alternative measures in reducing or mitigating impacts such as AMD and air pollution. Several studies have revealed how alumino-silicate mineral waste can be used as raw material to produce construction materials. This study aimed at evaluating the potential of synthesizing a geopolymer material from Musina copper mine tailings. Tailings were characterized for their physicochemical and mineralogical compositions using standard laboratory techniques in order to evaluate suitability in geopolymerization. First section of the results presented physicochemical and mineralogical characterization of the Musina copper tailings together with the bioavailability of the chemical species. It was observed that the tailings are mainly composed of SiO2 and Al2O3 as the major oxides indicating that they are aluminosilicate material. Mineralogical analysis revealed dominance of quartz, epidote and chlorite as the major minerals. The bioavailability assessment showed that largely Cu and Ca are bioavailable and highly soluble in an aqueous solution while Al, Mg, Ni, Co, Cr and Fe have a high proportion in non-labile phase. Second section presented the preliminary results wherein the potential application of Musina copper tailings in geopolymerization was evaluated. The results showed that Musina copper tailings can be used to synthesize a geopolymer material. However, it was recommended that several parameters influencing geopolymerization need to be evaluated. The third section presented the evaluation of optimum parameters that influence the geopolymerization process, which include type of alkali activators, alkali activator concentration, curing temperature, liquid-solid (L/S) ratio and curing regime. It was observed that a mixture of NaOH:Na2SiO3.5H20 at a ratio of 70:30 yields a better geopolymer material. The concentration of 10 M NaOH:Na2SiO3.5H20 at a ratio of 70:30 was observed to be the best that yielded the UCS that is acceptable according to SANS1215 standards. When evaluating curing regime, it was found that the material cured using greenhouse has lower UCS as compared to the material cured using oven. The v effect of temperature showed that the UCS decreases with increasing curing temperature. An admixture of river sand and cement was introduced which resulted in a high UCS of 21.16 MPa when using an admixture of cement. The mineralogical composition of the geopolymer bricks showed formation of secondary minerals such as phlogopite, fluorapatite, diopside and actinolite. Batch leaching conducted on the geopolymer bricks detected high leaching of Na from the bricks. Based on the findings of the study of the raw MT potential to produce geopolymer bricks, it was concluded that the material can be used to produce bricks that are within the SANS 1215 requirements. The study further recommended that the study a focus on using cylindrical moulds, other alkali activators and a mechanical mixer. It was also recommended that the greenhouse be restructured to contain heat within the greenhouse during the evening so as to allow constant temperature within
MENVSC
Department of Ecology and Resource Management
Keywords: Mine tailings; UCTD; Alumino-silicate; Acid mine drainage (AMD); Unified soil classification system (USCS); Semi-crystaline structure; 622.3430968257; Environmental monitoring -- South Africa -- Limpopo; Environmental impact analysis -- South Africa -- Limpopo; Mines and mineral resources --South Africa -- Limpopo; Copper mines and mining -- South Africa -- Limpopo; Tailings dams -- South Africa -- Limpopo; Acid mine drainage -- South Africa -- Limpopo; Mine drainage -- South Africa -- Limpopo; Dams -- South Africa -- Limpopo